Assessing the relationship between syringe exchange, pharmacy, and street sources of accessing syringes and injection drug use behavior in a pooled nationally representative sample of people who inject drugs in the United States from 2002 to 2019 - Phillip L. Marotta (BMC, 2021)
Abstract Provision of sterile syringes is an evidence-based strategy of reducing syringe sharing and reusing and yet, access to sterile syringes through pharmacies and syringe exchange programs (SEPs) in the United States remains inadequate. This nationally representative study examined associations between obtaining syringes from pharmacies, SEPs, and sterilizing syringes with bleach and risk of syringe borrowing, lending and reusing syringes in a pooled cross-sectional dataset of 1737 PWID from the 2002–2019 National Survey on Drug Use and Health. Logistic regression was used to produce odds ratios (OR) of the odds of injection drug behaviors after adjusting for obtaining syringes from SEPs, pharmacies, the street, and other sources and potential confounders of race, ethnicity, sex, education, and insurance coverage. Obtaining syringes through SEPs was associated with lower odds of borrowing (OR = .4, CI95% = .2, .9, p = .022) and reusing syringes (OR = .3, CI95% = .2, .6, < .001) compared to obtaining syringes on the street. Obtaining syringes from pharmacies was associated with lower odds of borrowing (OR = .5, CI95% = .3, .9, p = .037) and lending (OR = .5 CI95% = .3, .9, p = .020) syringes. Using bleach to clean syringes was associated with increased odds of borrowing (OR = 2.0, CI95% = 1.3, 3.0, p = .002), lending (OR = 2.0, CI95% = 1.3, 3.0, p = .002) and reusing syringes (OR = 2.4, CI95% = 1.6, 3.6, p < .001). Our findings support provision of syringes through pharmacies and SEPs as a gold-standard strategy of reducing sharing and reuse of syringes in the US.